Ekonomiczny aspekt antysemityzmu narodowej demokracji w jej walce o państwo narodowe w latach trzydziestych II RP - Sobczak, Mieczysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
From the beginning of the second Polish Republic (II RP) problems of the economy were very important for the National Democracy. "National Capital" was as important as a strong army. At this background the National Democracy considered the economic meaning of national minorities, especially Jews. After taking over a power by the "sanacja" regime and then during the years of Great Economic Crisis, the National Democracy had no doubt that Jews influence on the economy caused damages in the Polish development. Because of the fact that this influence was too strong, the National Democracy decided that it should be limited by the development of Polish (Christian) economic potential. Such thoughts deepened programmatic anti-Semitism of the National Democracy and sharpened Polish-Jewish conflict. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 64-85